West Bank and Gaza Public Expenditure Review : From Crisis to Greater Fiscal Independence, Volume 2 - World Bank (Washington, DC, 2012)
This report examines the fiscal crisis facing the Palestinian Authority (PA) that could threaten its very existence. It looks at recent macroeconomic and fiscal developments and gives and analysis of key issues and challenges such as economic and fiscal trends. The report also goes in depth analysis of the public financial management issues, the challenges of civil service reform, reforming intergovernmental fiscal relations, the education sector, and social policy and social safety nets. The report is divided into two volumes with volume one giving an overview with conclusions and recommendations, while volume gives an in depth look at the topics.